(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article analyzes requests for public information directed to Brazilian federal universities, between 2012 and 2019. The research questions that guide the investigation are: (i) what is the profile of individuals who request information from federal universities in Brazil?; (ii) what topics most interest applicants?; (iii) how has the distribution of requests occurred over time since the implementation of the Access to Information Law in 2012?; The descriptive analysis of the e-SIC portal reports shows that requests to universities are made by federal civil servants, students, professors or researchers. The requests come from male individuals, with complete higher education and belonging to the same region of the institution investigated. The most prominent themes are associated with higher education. The data indicates a significant growth in the number of requests sent to universities during the period analyzed.